HUBUNGAN PENGETAHUAN DAN PERILAKU HYGIENE SANITASI PEDAGANG JAJANAN DI SEKOLAH DASAR NEGERI KELURAHAN WATES KOTA MOJOKERTO - Bagus Kurniawan Romadhon; Henry Sudiyanto; Mohammad Yusuf Alamudi (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
The number of problems of school children's snacks when examined in terms of personal hygiene of sellers, how to store, how to serve, the quality of food and the habits of children snacking is still not good, Hygiene and Sanitation in food is a preventive activity from various kinds of diseases caused. This study is an observational study with a cross-sectional approach. The sample size that will be taken is 30 traders who sell in the area of public elementary schools in Wates Village, Mojokerto City. From the results of calculations with the Pearson correlation test, a significance value of 0.256 was obtained. If the significance value is> 0.05, it means that there is no correlation between knowledge and behavior of hawkers about hygiene and sanitation with a correlation value (0.214) categorized as a weak correlation with the basic Pearson correlation value of 0.21 to 0.40. From this study, it was found that there was a significant relationship between the knowledge and behavior of hawkers in the area of Wates Public Elementary School in Mojokerto city towards hygiene and sanitation. Knowledge and behavior of food hygiene and sanitation in hawkers in the area of public elementary schools in Wates village in Mojokerto city on average is poor. The results of this study are expected to be used as a reference in improving the quality of hygiene and sanitation of hawkers